2021
DOI: 10.1186/s12885-021-08686-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of the postoperative prognostic nutritional index in patients with glioblastoma: a retrospective study

Abstract: Background The prognostic nutritional index (PNI) reflects immunonutritional status. We evaluated the effects of postoperative PNI and perioperative changes in the PNI on overall survival (OS) in glioblastoma (GBM) patients. Methods Demographic, laboratory, and clinical data were retrospectively collected from 335 GBM patients. Preoperative and postoperative PNIs were calculated from serum albumin concentration and lymphocyte count, which were meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…At the same time, even in the case of patients with high PNI before PORT, maintaining optimal PNI may be important. Prior studies that focused on pre‐ or postoperative PNI have proposed perioperative interventions such as nutritional support or pulmonary rehabilitation to improve postoperative PNI 7,10,24 . However, such perioperative interventions alone might not be sufficient for patients receiving PORT, as immunonutritional status can still be affected by postoperative treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, even in the case of patients with high PNI before PORT, maintaining optimal PNI may be important. Prior studies that focused on pre‐ or postoperative PNI have proposed perioperative interventions such as nutritional support or pulmonary rehabilitation to improve postoperative PNI 7,10,24 . However, such perioperative interventions alone might not be sufficient for patients receiving PORT, as immunonutritional status can still be affected by postoperative treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies have focused on the role of pretreatment PNI, but immunonutritional status can change dramatically after surgery, chemotherapy, and radiotherapy. A few studies have incorporated both pre‐ and post‐treatment PNI and found PNI after surgery or chemotherapy also has a significant impact on survival of NSCLC patients 7,8 as well as those with glioblastoma, renal cell carcinoma, and breast cancer 9–11 . However, to date, there have been no studies of the relationship between PNI and PORT in NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21,24] Postoperatively high PNI also showed improved OS and perioperative changes in PNI provides additional important information for prognostic prediction in GBM patients. [25] The decision to resection the brains of metastatic patients must be made urgently but carefully because surgery can potentially cause morbidity and mortality. The increased level of neutrophils suppresses the cytolytic activity of lymphocytes and activated T cells.…”
Section: Discussionmentioning
confidence: 99%